PENGARUH SUHU PEMBAKARAN ABU SEKAM PADI SEBAGAI SUBTITUSI SEMEN PADA BETON SCC - Nugraha, Ivan; Firdaus, Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This study analyzes the effect of combustion temperature of Rice Husk Ash (RHA) as a 10% cement substitute on the performance of Self Compacting Concrete (SCC). An experimental method was applied by burning RHA at 400°C, 500°C, and 600°C, followed by testing fresh properties (filling ability, passing ability, segregation resistance), compressive strength at 7, 14, and 28 days, as well as splitting tensile strength and modulus of elasticity at 28 days. Results confirmed all mixtures met SCC criteria (EFNARC 2005). RHA burned at 600°C yielded the highest compressive strength (18.05 MPa at 7 days; 22.29 MPa at 14 days; 39.07 MPa at 28 days), splitting tensile strength (3.41 MPa), and modulus of elasticity (22,478.25 MPa), exceeding normal concrete. However, higher combustion temperatures reduced flowability (RHA600: 55.3 cm) and passing ability (RHA600: 0.872) while enhancing segregation resistance (15 seconds). It is concluded that 10% substitution of RHA burned at 600°C significantly improves the mechanical properties of SCC despite a slight reduction in workability.Keywords: Rice Husk Ash (RHA), Combustion Temperature, Compressive Strength, Splitting Tensile Strength, Modulus of Elasticity.